Family knowledge and practices in the management of dengue in the Trece de Mayo settlement: a pilot test (Boletín Semillero de Investigación en Familia, 2021)
According to PAHO, the active participation of society is considered a key element in the fight against dengue. It is important to promote greater commitment and integration among people to raise awareness of the dengue problem and be participants in the solution of the disease provided by the mosquito bite. Research objective to identify the knowledge and practices of the family in the management of dengue in the thirteenth of May settlement of the municipality of Villavicencio[1]Meta in order to generate strategies for the control of the disease. Method through a descriptive study with qualitative variables and quantitative variables. Methodology from the qualitative point of view, the focused ethnographic tool was used using the semi-structured interview and the field diary, and for the qualitative one, the descriptive research with instruments that allowed to assess knowledge, attitudes and practices and a sociodemographic survey. Relevance the family has a high level because they affirm that the main means of prevention are: fumigation, not leaving water in containers, using mosquito net, affirming that water tanks should not be maintained because this vector spreads. Conclusion It is important for the family to participate in the campaigns they carry out in the community or to be promoters of leading campaigns for the management of dengue and recognize that sociodemographic factors are essential to achieve adequate control of the disease.
Keywords: Disease; Family; Knowledge; Community; Biologic control